Applying Systems Thinking Concepts for the Analysis of Digital Excise Stamp Transformation in Indonesia - Afifah Nur Ismawati; Akhmad Hidayatno (Green Publisher Indonesia, 2026)
The increasing complexity of illicit trade and excise violations has become a major challenge for governments in protecting state revenue and ensuring product legality. In Indonesia, excise violations involving tobacco and alcoholic products have continued to increase, with cases rising from 12,045 in 2021 to 21,915 in 2024, resulting in significant potential revenue losses. Digital excise stamp transformation is considered a strategic solution to improve traceability, transparency, compliance, and monitoring effectiveness. However, its implementation involves complex interactions among technological adoption, system security, industry readiness, institutional capacity, and enforcement mechanisms. This study aims to analyze the dynamics of digital excise stamp transformation in Indonesia and identify strategic intervention points for sustainable implementation using a systems thinking approach. The research employed a qualitative systems thinking method consisting of a Systematic Literature Review (SLR), conceptual model development, causal loop diagram (CLD) construction, model verification and validation through Focus Group Discussions (FGDs), and system archetype analysis. The results revealed three main feedback structures: two reinforcing loops related to user experience investment and security investment, and one balancing loop associated with enforcement effectiveness and institutional operational burden. The analysis identified several systemic challenges, including limits to growth, fixes that fail, and growth underinvestment archetypes. The study concludes that successful digital excise stamp implementation requires integrated policies focusing on technology adoption, security enhancement, institutional capacity development, and risk-based enforcement strategies to ensure long-term sustainability and optimize government revenue protection.